2018
DOI: 10.1152/ajprenal.00109.2017
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in renin-angiotensin-aldosterone system affect extracellular volume in healthy subjects

Abstract: Several studies reported sex differences in aldosterone. It is unknown whether these differences are associated with differences in volume regulation. Therefore we studied both aldosterone and extracellular volume in men and women on different sodium intakes. In healthy normotensive men ( n = 18) and premenopausal women ( n = 18) we investigated plasma aldosterone, blood pressure, and extracellular volume (I-iothalamate), during both low (target intake 50 mmol Na/day) and high sodium intake (target intake 200 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 30 publications
2
30
0
Order By: Relevance
“…However, the results from our stratified analysis contradicted this explanation. Again, sex differences in hormone regulation, with lower levels of aldosterone in premenopausal women than in men and, therefore, a greater risk of overtreatment, might account for our findings (44, 45).…”
Section: Discussionmentioning
confidence: 67%
“…However, the results from our stratified analysis contradicted this explanation. Again, sex differences in hormone regulation, with lower levels of aldosterone in premenopausal women than in men and, therefore, a greater risk of overtreatment, might account for our findings (44, 45).…”
Section: Discussionmentioning
confidence: 67%
“…[14][15][16] In the renal vasculature, P2 receptor agonism increases renal vascular resistance [17][18][19] and promotes renin secretion from JG cells. [20][21][22][23][24] In contrast, P1 receptor agonism mediates tubuloglomerular feedback and suppression of renin secretion in a calcium-dependent manner. [25][26][27][28][29][30] Thus, ATP accumulation and degradation controls differential actions on renin secretion.…”
mentioning
confidence: 99%
“…Discordant with the Framingham Heart Study findings, we found a 17–18% higher aldosterone among men in the JHS independent of aldosterone altering medications. A recent study by Toering et al among whites showed that men on a high-salt diet (4.6 grams/day) had higher serum aldosterone than women, with no aldosterone sex differences on a low-salt diet [22]. In the JHS, the average dietary sodium intake was 3.5 grams per day [5], much closer to the high-salt diet in the study, and thus our finding of higher aldosterone in men is consistent with this study, but does not explain the greater magnitude of association of higher LS7 score with lower aldosterone among women.…”
Section: Discussionmentioning
confidence: 99%
“…In the JHS, the average dietary sodium intake was 3.5 grams per day [5], much closer to the high-salt diet in the study, and thus our finding of higher aldosterone in men is consistent with this study, but does not explain the greater magnitude of association of higher LS7 score with lower aldosterone among women. Toering et al also evaluated the adrenal response to exogenous angiotensin II which was significantly higher in women [22]. Thus, there may be sex differences in the regulation of aldosterone with greater biological adrenal responsiveness among women.…”
Section: Discussionmentioning
confidence: 99%